Cross Matching Learning Outcomes of Postgraduate Basic Medical Sciences to the Qualification Framework of Pakistan - Huma, Zilli; Baseer, Najma; Mahboob, Usman (ADVANCES IN BASIC MEDICAL SCIENCES, 2020)
Objective: To match the learning outcomes defined in PhD course document to guidelines provided by the HEC in terms of both the Pakistan Qualification Framework (PQF) and the National Qualification Framework (NQF). Methodology: A qualitative study by comparative content analysis, carried out at Khyber Medical University in 2016. The learning outcomes in PQF and NQF were defined by purposive sampling based on three major domains of learning; Knowledge, Skills, and application of skills, and matched to the PhD Course guidelines. Results: Cross referencing the documents showed that on manifest analysis the coverage for knowledge and skills ranged from 28 to 36 % but with latent analysis it was bumped up to 160 to 56 %, respectively. Research showed an excellent match in the PQF with 175% but for the NQF it reaches 75% only. Conclusion: Although there is some degree of manifest and a larger degree of latent compatibility as regards the first two domains of Knowledge and Skills, the third component of applicability was entirely deficient. Keeping in focus research as a major component, explicit outcomes on generic skills should be added to address this gap. Key words: Learning outcomes, Curriculum matching, Content analysis, Manifest analysis, Latent analysis, Qualification framework